Review of Active and Passive Daylighting Technologies for Sustainable Building - Nneka Obianuju Onubogu; Kok-Keong Chong; Ming-Hui Tan (International Journal of Photoenergy)
According to the International Energy Agency, nearly 20% of worldwide electricity is used up by lighting. This is equal to the total electricity nuclear power generates. Thus, it is needy to explore new technologies for direct use of sunlight via integrating daylight system to the building, which is cost-saving, environment-friendly, and a green solution rather than indirect conversion of electricity to lighting even from renewable sources. In this paper, we present a review on the existing technologies of daylighting systems up to date and how they can provide lighting in a building interior via collection and distribution of sunlight. Our review is a comprehensive study to embrace both passive daylighting system with stationary design and active daylighting system equipped with sun tracking. The economic feasibility, general challenges, and prospects of daylighting systems are also discussed to understand the existing problems that hinder the extensive deployment of daylighting systems. In conclusion, more research works are needed in improving the technological development of a daylighting system so that it is more affordable, environment-friendly, less energy-intensive, and easy to install and gives uniform illumination for the effective application in both commercial building and residential houses.